Kajian Nilai Energi Metabolis Biji Sorghum Melalui Teknologi Sangrai Pada Ayam Petelur Periode Afkir - Hanny Indrat Wahyuni; Retno Iswarin Pujaningsih; Padwi Anwar Sayekti (Jurnal Agripet, 2008)
Evaluation of metabolic energy value of roasted sorghum in culled laying chickensABSTRACT. Tannin contained in sorghum can be reduced by using technology processing such as roasting. By using this way, husk of sorghum can be removed leading to decrease of tannin content which is reflected by the value of metabolism energy. The purpose of this experiment is to investigate the effect of roasted sorghum on metabolism energy of culled laying chickens. Measurement of metabolic energy as mathematic is used as comparison. The material used in his experiment was red sorghum, water, and 39 culled laying chickens. Equipment used in this experiment was balance, roasting tool, plastic, force feeding equipment, metabolism cages and bomb calori-meter. This experiment used completely randomized design consisting of 4 treatments and 4 replications (each replication 3 chickens). Treatment consisted of T0 = no roasted sorghum, T1 = roasted for 5 minutes and T2 = roasted for 10 minutes. Data collected were metabolism energy of roasted sorghum both biologically (force feeding) and mathematically (proximate analysis) at culled laying chickens. All data were statistically calculated, further statistically was conducted by using Duncan and compression of metabolism energy was calculated by using t-Test. The results show that, no statistically effect (p0, 05) on duration of roasting on metabolism energy of sorghum. Based on t-Test analysis, there was a significantly difference (p0, 05) between biological metabolism and mathematical metabolism. From this experiment, it can be concluded that 10 minutes of roasting cannot increase of sorghum metabolic energy. The average of biological metabolic was lower (3105, 94 kcal/kg) compared to the average of mathematical metabolic energy (3766, 82 kcal/kg).